Host Transcriptional Response of Sclerotinia sclerotiorum Induced by the Mycoparasite Coniothyrium minitans - Zhao, Huizhang; Zhou, Ting; Xie, Jiatao; Cheng, Jiasen; Jiang, Daohong; Fu, Yanping (Frontiers in Microbiology, 2020)
Mycoparasite Coniothyrium minitans parasitizes specifically the mycelia or sclerotia of Sclerotinia sclerotiorum, a worldwidely spread plant fungal pathogen causing serious diseases on crops. The interaction of C. minitans with S. sclerotiorum remains reciprocal and complex and little is known, especially on the side of the host (S. sclerotiorum). In this study, the early transcriptional response of S. sclerotiorum to the mycoparasitism of C. minitans was explored and the DEGs were analyzed. Based on GO ontology, KEGG pathway and fungal categories database, 887 up-regulated DEGs were enriched in the growth related function (i.e. rRNA processing, ribosome biogenesis, binding and transport), while the 546 down-regulated DEGs were enriched in the stress-related functions (i.e. oxidoreductase, response to stress and heat and the chorismate biosynthetic process). The expression of shikimate pathway and the biosynthesis of phenylalanine involving genes was significantly suppressed. Furthermore, 581 unenriched DEGs were explored in the parasitizing process and were mapped on the Pfam domains of redox enzymes, Alpha/Beta hydrolase, haloacid dehalogenase, and other universal conserved domain containing proteins. Thirty-two DEGs encoding candidate effectors, with 16 up-regulated and 16 down-regulated, were observed with diverse function. SS1G_11912 (encoding SsNEP2) was significantly up-regulated and may function in the parasitism. The involving of the shikimate pathway of phenylalanine biosynthesis and effector candidates were discussed. The results provide a basal understand on the interaction of S. sclerotiorum and C. minitans.